2009
DOI: 10.1097/aln.0b013e3181a4c6b9
|View full text |Cite
|
Sign up to set email alerts
|

Crossover Comparison of the Laryngeal Mask Supreme™ and the i-gel™ in Simulated Difficult Airway Scenario in Anesthetized Patients

Abstract: Both airway devices had similar insertion success and clinical performance in the simulated difficult airway situation. The authors found less epiglottic downfolding and better fiberoptic view but longer insertion time with the i-gel. Our study shows that both devices are feasible for emergency airway management in patients with reduced neck movement and limited mouth opening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
127
4
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(152 citation statements)
references
References 35 publications
17
127
4
4
Order By: Relevance
“…We assume that relatively larger size SLMA might have been the cause of difficult insertion in those 3 cases. The range of insertion time (TOI) in our study was 11-15 seconds, which is supported by similar findings by Verghese C et al [7] , Cook TM et al [11] and Theiler LG et al [14] . We think that the intelligent design of the fixation tube (FT) along with the elliptical and anatomically shaped semi rigid airway tube of the SLMA facilitated rapid insertion.…”
Section: Discussionsupporting
confidence: 80%
“…We assume that relatively larger size SLMA might have been the cause of difficult insertion in those 3 cases. The range of insertion time (TOI) in our study was 11-15 seconds, which is supported by similar findings by Verghese C et al [7] , Cook TM et al [11] and Theiler LG et al [14] . We think that the intelligent design of the fixation tube (FT) along with the elliptical and anatomically shaped semi rigid airway tube of the SLMA facilitated rapid insertion.…”
Section: Discussionsupporting
confidence: 80%
“…In clinical trials, the SLMA has been found comparable with the reusable LMA ProSeal TM (PLMA), 1 with the SLMA having a higher rate of success on first attempt insertion. [2][3][4][5] Previous studies have shown the use of the PLMA and SLMA in non-paralyzed patients, 6 in anesthetized patients with a simulated difficult airway, 7 and in patients undergoing laparoscopy procedures. 8,9 More recent studies and case reports have shown that it is effective in providing ventilation and oxygenation in challenging cases, such as the morbidly obese patients, 10 patients in the prone position, 11,12 and those who have suffered from multiple trauma.…”
Section: Résumémentioning
confidence: 99%
“…Six of the studies compared the LMA Supreme with the LMA Proseal. 10,[13][14][15][16][17] The remaining studies compared the LMA Supreme with the LMA Classic, 23 i-gel, [18][19][20] facemask, 21 or endotracheal tube. 22 In the six RCTs comparing the LMA Supreme with the LMA Proseal, 418 patients were identified and 295 (70%) of those were female.…”
Section: Use Of Lma Supreme In Normal Airway/elective Surgerymentioning
confidence: 99%
“…[18][19][20] Two hundred fifty patients were identified and 191 (76%) of those were female. All patients were undergoing elective surgery.…”
Section: Comparison Of the Lma Supreme And I-gelmentioning
confidence: 99%